PERANCANGAN APLIKASI MEDIA INFORMASI LOWONGAN KERJA PERUSAHAAN BAGI PENCARI KERJA BERBASIS ANDROID - Yanto, Indra Yanto; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2022)
Work is an activity carried out by both parties, namely the employer and the recipient of work which aims to meet the needs of employees. However, not everyone has the opportunity to get a job. Batam's high unemployment rate causes economic growth to slow down. In looking for a job, information is needed in the form of job vacancies that are guided by today's times. This job vacancy application will make it easier for job seekers to get a decent job.